제천 약초시장 이전 타당성 조사 및 기본계획 수립 - 조명기 (한국농촌경제연구원, 2007)
Je-Cheon city is the cluster area of traditional medicine industry according to the 5 year plan of national balance development. The city is a distribution center of traditional medicine stuffs as cluster of traditional oriental medicine constructed already. Also, Je-Cheon city is gathering and distributing traditional medicine stuffs of vast quantity and high quality cultivated from areas like Chung-Buk, Gang-Won and Gyeong-Buk. Specially Astragalus which is produced most plentifully from Je-Cheon area hold 80% of production and distribution quantity in the entire country. Solomn's seal hold 96% of production and distribution quantity in the entire country. The city distributes approximately 40% of traditional medicine stuffs in the entire country. Existing medical plant market is in stagnation condition due to a lack of place. Consequently, this research is needed to develop the medical plant market. Specially the 2010 Je-Cheon International Traditional oriental medicine Expo will be held successfully as activating the medical plant market. And plan to relocate the market to Expo site is reviewed positively in terms of economy. The movement is one of the strategies to be a specialized traditional oriental medicine city and to hold the Je-Cheon International Traditional oriental medicine Expo. We analyzed movement propriety by rasing problems about Existing medical plant market taking charge of important roles of the 2010 Je-Cheon International Traditional oriental medicine Expo and traditional oriental medicine industry complex. Concerning the movement of the medical plant market, our purpose is to establish basic plans of the medical plant market such as appropriate size, proper placement plan, reasonable business expense, marketing strategy. In the light of summarizing main contents in the study, in the 2nd chapter, through the SWOT analysis of medical plant industry in Je-Cheon, facing problems which will be experienced was dealt with. In the 3rd chapter, actual condition of production and distribution on the medical plant in the area was analyzed. In the 4th chapter, necessity and direction on movement of the medical plant market was reviewed. In the 5th chapter, basic construction plan to the composite distribution facility complex on medical plant was presented. In the 6th chapter, turnover, facility size and presumption of construction expense on the composite distribution facility complex was presented. In the 7th chapter, analysis of financial propriety on the composite distribution facility complex was presented. In the 8th chapter, business propulsion, plan of management and operation on the composite distribution facility complex was presented. In the 9th chapter, proper placement plan of facility was presented. Lastly, marketing strategy and activation plan on the composite distribution facility complex was presented. Researchers: Cho Myung-Ki, Jeon Chang-Gon, Byeon Sin-Eui